The status and predictors of self‐care among older adults with hypertension in China using the Chinese version of Self‐Care of Hypertension Inventory – A cross‐sectional study - Yu‐Jie Guo; Xiao‐Yun Hu; Hong‐Juan Ji; Qiao Zhao; Long‐Yuan Wang; Xiao‐Yan Zhou; Jue Tang; Lei Yang; Xiang‐Chao Sun (Nursing Open, 2022)
Abstract Aim To investigate the status and predictors of self‐care among older adults with hypertension in China by the Chinese version of Self‐Care of Hypertension Inventory. Design A cross‐sectional questionnaire survey. Methods A convenience sampling of 544 older adults with hypertension was surveyed using the Chinese version of Self‐Care of Hypertension Inventory. SPSS25.0 software was used for statistical analysis of the data. Generalized liner model univariate analysis and the optimal scaling regression analysis were performed to investigate the predictors of self‐care. Results The status of self‐care was poor with the median and inter‐quartile range of total scores of self‐care (140.00 ± 67), the scores of self‐care maintenance (50 ± 24.76), the scores of self‐care management (56.25 ± 29.41) and the scores of self‐care confidence (54.79 ± 29.17). Age, family model, primary caregiver, maximum systolic blood pressure, coverage of medical insurance, disease duration, receiving self‐care education, education level, economic burden and family history of hypertension were the most powerful predictors of self‐care among older adults with hypertension.